Pada Remaja, Kebencian terhadap Diri Sendiri, dapat Memicu Perilaku Toxic Disinhibition Online - Maharani Ardi Putri; Muhamad Desta Pratama; M. Ramadhana R. (Jurnal Ilmiah Psikologi MIND SET, 2023)
In the digital era, aggressiveness can be shown in Toxic Disinhibition Online behavior, where people can curse, bully, and pressure their co-stars both verbally and psychologically while online. A lot of people do not realize that the aggressive behavior displayed is influenced by self-hatred, the same goes for Toxic Disinhibition Online's behavior. This study looks at how self-hate can be related to the emergence of Toxic Disinhibition Online behavior. This study looks at how self-hate can be related to the emergence of Toxic Disinhibition Online behavior. Measurements were taken on 115 teenagers who played online games, and used the Online Disinhibition Scale and the Self-Hate Scale. The result is that Self-Hate has an effect of 7.5% on Toxic Disinhibition Online, in a positive direction. This means, when a teenager does not like or hate himself, then there is a possibility that he will display Toxic Disinhibition Online's aggressive behavior when playing online games.